Teratoma in Infants and Children - Fathollah Roshanzamir; Javad Ghoroubi; Alireza Mirshemirani; Ahmad Khaleghnejad Tabari; Mohsen Rouzrokh; Mehrdad Izadi; Leili Mohajerzadeh; Alireza Mahdavi; Mehdi Sarafi (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Background: Teratomas arise from three germ cell layers, the ectoderm, endoderm and mesoderm1, 2, and have several degrees of differentiation. We report our experience with teratomas at a tertiary pediatric surgery center. Patients and Methods: The hospital records of all patients with the pathological diagnosis of teratoma treated during 10 years between 2004 and 2014 were reviewed and the following information was obtained: Sex, site of tumor, treatment and outcome. Results: Sixty seven patients consisting of 49 girls (73%) and 18 boys (27%) were treated with teratomas at various sites of the body. These included: sacrococcygeal (SC) 32 patients (27 females& 5 males), ovarian 12 cases, cervical 4 patients (1 females & 3 males), retroperitoneal 9 (5 females & 4 males), Nasopharyngeal 2 patients both of which were females, mediastinal 2 cases (1 female & 1 male) and 5 testicular teratoma patients. All patients underwent surgery, and the most common procedure was total resection in 63(94%) of patients. Twenty eight (42%) received chemotherapy. In follow-up 52(77%) patients were in complete remission, 8(12%) had died, and 4 cases did not attend follow-up visits. Conclusions: Teratomas are a group of tumors with similar histological picture but different behaviors. Sacrococcygeal teratomas are the commonest and the majorities are benign but the risk of malignant transformation increases with age. Management of teratomas is a combination of surgery and chemotherapy which may lead patients to a better prognosis.